Exploring the role of sex and maturation in a bio-banding competition: Insights into pre-competition anxiety in youth handball - de la Rubia, A.; García Sánchez, C.; Marquina, M.; Martín Castellano, A.; Lino Samaniego, Á.; Tannion, K. (Elsevier, 2025)
Objective The present study analysed the impact of biological maturity status and sex on pre-competitive anxiety, self-confidence and perception in young handball players under the bio-banding competition. Equipment and methods The sample consisted of 87 handball players (46 boys and 41 girls) aged 13¿17 years. Anthropometric data (height, body mass and self-reported biological parent's height) were collected to calculate maturity level using the percentage of predicted adult height (Khamis-Roche equation). The players were classified as early, on-time and late maturers (Z-score distribution). Furthermore, a psychological assessment was carried out using a validated Spanish version of the CSAI-2R and a post-competition perception questionnaire. Multivariate analyses (MANOVA) were conducted to estimate the impact of sex and biological maturity status on psychological constructs and perception. Results Higher cognitive and somatic anxiety levels in girls (P < 0.05, both) and self-confidence in boys (P < 0.001) were found. Moreover, higher cognitive anxiety levels were identified in early maturing girls than in on-time maturing girls (P < 0.05). According to the bio-banding perception, boys showed higher understanding (P < 0.001) and enjoyment (P < 0.05) levels. In girls, late maturing girls showed higher enjoyment levels than the rest of the counterparts (P < 0.05). Furthermore, enjoyment and self-confidence were positively correlated (P < 0.01). Conclusions The findings suggest that bio-banding may offer a valuable strategy for creating equitable competitive environments by aligning challenges with players¿ maturity status. Practical recommendations include tailoring competitive experiences, addressing psychological needs ¿ particularly in female athletes ¿ and fostering safe developmental pathways. These insights provide actionable guidance for coaches and stakeholders to enhance the effectiveness of talent identification and development programs.
Keywords: Maturity ; Sex ; Anxiety ; Self-confidence ; Team sports